Maqasidi Interpretation of Maysir Verses: Ethics and Regulation of Lootbox Video Games - Fauzi, Muhammad Iqbal; Yunus, Badruzzaman M. (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2025)
This paper discusses the interpretation of maqasidi on maysir verses and their relevance to the ethics and regulation of Lootbox video games. The methodology used in this study is the Descriptive Analysis method of Literature Study. Based on quotes from Islamic primary sources and pre-Islamic Arabic poetry, contextualization and reconstruction of betting practices in that period are carried out. Assets, people, and instruments used during gambling are determined, such as: ğuzūr, aysār, qidāḥ, rabāba, ĥurda, raqīb and the like. Propositions are explained by playing tens, twenty-eight and other types of gambling. The significance of maysir is shown, which is the basis for the stance of contemporary Islamic jurists on the (un)acceptability of current forms of games and entertainment. Understanding the path of gambling at that time helps to standardize modern gambling practices appropriately. The results of this study are that we can say that the Lootbox video game platform or system is a financial tool comparable to gambling, or more precisely, disguised gambling. This is because transactions on the Lootbox video game platform comply with the four criteria of gambling that have been established by scholars: there is a bettor, an asset at stake, a winner and a loser, and the winner has the right to the loser's asset.